Use of Web-Based Calculator for the Implementation of ACR TI-RADS Risk-Stratification System. - Ng, Yee Seng; Quadri, Bilal; Baker, Chris; Foster, Christopher; McColl, Roderick W.; Fetzer, David T.; Peshock, Ronald M.; Browning, Travis (Journal of Digital Imaging, 2022)
In this article, we demonstrate the use of a software-based radiologist reporting tool for the implementation of American College of Radiology Thyroid Imaging, Reporting and Data System thyroid nodule risk-stratification. The technical details are described with emphasis on addressing the information security and patient privacy issues while allowing it to integrate with the electronic health record and radiology reporting dictation software. Its practical implementation is assessed in a quality improvement project in which guideline adherence and recommendation congruence were measured pre and post implementation. The descriptions of our solution and the release of the open-sourced codes may be helpful in future implementation of similar web-based calculators.